Characterization of plasmid mediated quinolone resistance genes in Enterobacteriaceae in a University Hospital in Tunisia - Sana Bahri; Sabrine Jarbouii; Ikram El Ahmer; Aniss Bel Haj Khalifa; Mohamed Khedher; Mahjoub Aouni; Olfa Bouallegue; Wejdene Mansour (Microbes and Infectious Diseases)
Background: Quinolone-resistant enterobacterial isolates have spread largely across hospitals and community in last years. In Tunisia, numerous studies describe the emergence of plasmid mediated quinolone resistance (PMQR) genes among Enterobacteriaceae. Objectives: Detection of PMQR genes among a collection of enetrobacterial isolates recovered in the Tahar Sfar University hospital in Tunisia and in the community. Methods: In vitro antimicrobial susceptibility testing, extended-spectrum β-lactamases, and PMQR genes were detected using PCR. Clonality of isolates was assessed by ERIC-PCR. Results: In this work, 1710 enterobacterial isolates were recovered in the Tahar Sfar University Hospital in Tunisia between January 2012 and March 2013. Eighty of them were resistant to nalidixic acid: 61 isolates  and 19 isolates were isolated from nosocomial and community cases respectively. Detection of PMQR genes leads to the identification of 7 and 8 QnrB producers in nosocomial and community acquired strains respectively. The qnrS PMQR gene was less present with 5/61 cases in nosocomial starins and 1/19 case in community one. The most predominant ESBL was the CTX-M-type one. According to ERIC-PCR profiles, we note a multiclonal dissemination with 12 different profiles in hospital-acquired strains and 9 profiles in community enterobacterial isolates. Conclusion: This result re-emphasize the widely distribution of the QNRB genes and their role in resistance to fluoroquinolones.